Review of the Internal Structure, Psychometric Properties, and Measurement Invariance of the Work-Related Rumination Scale – Spanish Version - Rosario-Hernández, Ernesto; Rovira-Millán, Lillian V.; Merino-Soto, César (Frontiers in Psychology, 2021)
Background: The aim of the current study was to examine the internal structure and assess the psychometric properties of the Work-Related Rumination Scale (WRRS) – Spanish version in a Puerto Rican sample of workers. This instrument is a 15-item questionnaire, which has three component or dimensions, affective rumination, problem-solving pondering, and detachment. This measure is used in the occupational health psychology context; however, there is little evidence of its psychometric properties. Materials and Methods: A total sample of 4,100 from five different study samples was used in this cross-sectional study design in which the WRRS was used. We conducted confirmatory factor analysis (CFA) and exploratory structural equation modeling (ESEM) to examine the internal structure of the Work-Related Rumination Scale. Measurement invariance across sex and age was examined. Results: The three-factor model was supported; however, four items were eliminated due to their cross-loadings and factorial complexity. This 11-item version of the WRRS was invariant across sex and age. Reliability of the three-factors of WRRS were within the range of .74 to .87 using Cronbach’s alpha and McDonald’s omega. Correlations between the three factors were as expected as well as with other established measures. Conclusion: The results suggest that the WRRS-Spanish version appears to be a reliable and valid instrument to measure work-related rumination using its three components. Comparison across sex and age appear to be useful in occupational health psychology research setting since results suggest that the WRRS is invariant regarding those variables.